EKPHRASTIC POETRY AND INDIAN MINIATURE PAINTINGS: ARTISTRY AND AESTHETICS OF DEBASISH LAHIRI’S TETHER THAT LIGHT - Mukherjee, Pradipta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
For an internationally acclaimed Indian English poet, Debasish Lahiri, time is a recording of the lingering of light, in nature, in the mind. His recent collection of poems, Tether that Light (2022) is an attempt to follow that trail of light left in selected Indian miniature paintings, particularly Mughal, Rajasthani, Pahari, and Deccani paintings. The intricate artworks and enchanting visuals of these incredible canvases have enthralled the poet who uses the treasure trove of Indian miniatures that work as intertexts for his ekphrastic collection of poems. Given the pictorial effect of words appearing as miniature paintings, the flawless transformation from one medium to the other, Lahiri’s symbiosis between literary texts and performing arts, poetry, and painting, foregrounds how concepts, attitudes, and ideologies operate across a broader cultural spectrum that is not exclusively literary. Transcending the borders of time and space, Tether that Light not only makes way for a larger interdisciplinarity between sister arts but opens up new avenues for interrogating notions of historicity, textuality and appropriations.